1997
DOI: 10.1038/sj.bjp.0701152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐1β, tumour necrosis factor‐α and interferon‐γ on the induction of cyclo‐oxygenase‐2 in cultured human airway smooth muscle cells

Abstract: 1 Increased levels of several pro-in¯ammatory cytokines including interleukin-1b (IL-1b) and tumour necrosis factor-a (TNFa) have been found in bronchoalveolar lavage¯uid from symptomatic asthmatic patients. are known to stimulate a number of cells to produce in¯ammatory mediators such as prostaglandins. Although airway smooth muscle (ASM) is known to be a rich source of prostaglandins, the regulation of cyclo-oxygenase (COX) isoforms and prostanoid production by proin¯ammatory cytokines have not been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
178
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 36 publications
(62 reference statements)
14
178
1
1
Order By: Relevance
“…This was not affected by cordycepin treatment. Because TNF does not induce the important inflammatory gene PTGS2 (COX2) in these cells (Pang and Knox 1997), we treated ASM cells with interleukin 1b after a 30-min preincubation with different doses of cordycepin, and found that PTGS2 mRNA induction is also very sensitive to cordycepin treatment (Fig. 3B).…”
Section: Cordycepin-terminated Poly(a) Tails Appear Not To Accumulatementioning
confidence: 99%
See 1 more Smart Citation
“…This was not affected by cordycepin treatment. Because TNF does not induce the important inflammatory gene PTGS2 (COX2) in these cells (Pang and Knox 1997), we treated ASM cells with interleukin 1b after a 30-min preincubation with different doses of cordycepin, and found that PTGS2 mRNA induction is also very sensitive to cordycepin treatment (Fig. 3B).…”
Section: Cordycepin-terminated Poly(a) Tails Appear Not To Accumulatementioning
confidence: 99%
“…HeLa and A549 lung epithelial carcinoma cells were cultured in DMEM with 10% fetal bovine serum with 4.5 g/L of glucose and 4 mM glutamine. Primary cultures from human airway smooth muscle cells (ASM) were prepared from explants as described previously (Pang and Knox 1997). The cells were cultured in DMEM supplemented with 10% fetal bovine serum, 100 U/mL penicillin, 0.1 mg/mL streptomycin, 0.025 mg/mL amphotericin B, and 4 mM L-glutamine.…”
Section: Reagentsmentioning
confidence: 99%
“…Cells at passage 3 were used for all experiments. The authors have previously shown that cells grown in this manner show the immunohistochemical and light microscopic characteristics of pure HASM cells [22].…”
Section: Cell Culturementioning
confidence: 99%
“…Primary cultures of adult HASM cells were prepared from explants of airway smooth muscle according to methods previously reported [22,23,30]. Briefly, human trachea was obtained from two post mortem individuals (one male aged 44 yrs and one female aged 52 yrs, with no evidence of airway disease) within 12 h of death.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation